2020
DOI: 10.3390/su12166521
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Urban Surfaces and Heat Islands in Nanjing during 1984–2018

Abstract: One of the many consequences of urbanization is the expansion of cities into rural areas, which leads to the transformation of lands from natural surfaces to developed surfaces. It is widely considered an established fact that urbanization generally increases the heat island effect. The objective of this study is to understand the pattern of urban surface transformation in the city of Nanjing since 1980 and to find, if any, the correlation between such transformation and the urban heat island effect. The super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…As a result, many studies have been conducted on the formation of the heat island effect: Zou et al (2021) experimentally found that increasing the natural subsurface cover can reduce the intensity and warming potential of the UHI effect; Li, Zhang et al (2020) attributed the formation of the heat island effect to structural changes in the subsurface due to urbanization and found through their study that aerosols affect the UHI; Liang et al (2021) simulated the effect of fine-scale urban subsurface on the urban heat island effect in Beijing and found that near-surface temperature was negatively correlated with emissivity/albedo and that near-surface temperature was positively correlated with urban fraction; The correlation between subsurface transformation and heat island effect was established by analytical and statistical methods by Li, Zhang et al (2020). In terms of general trends, the urban heat island effect is positively correlated with the expansion of hard surfaces and the deterioration of green surfaces and water bodies (Li, Zhang et al, 2020). Various studies now show that the subsurface factor is the main reason for the formation of the heat island effect.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many studies have been conducted on the formation of the heat island effect: Zou et al (2021) experimentally found that increasing the natural subsurface cover can reduce the intensity and warming potential of the UHI effect; Li, Zhang et al (2020) attributed the formation of the heat island effect to structural changes in the subsurface due to urbanization and found through their study that aerosols affect the UHI; Liang et al (2021) simulated the effect of fine-scale urban subsurface on the urban heat island effect in Beijing and found that near-surface temperature was negatively correlated with emissivity/albedo and that near-surface temperature was positively correlated with urban fraction; The correlation between subsurface transformation and heat island effect was established by analytical and statistical methods by Li, Zhang et al (2020). In terms of general trends, the urban heat island effect is positively correlated with the expansion of hard surfaces and the deterioration of green surfaces and water bodies (Li, Zhang et al, 2020). Various studies now show that the subsurface factor is the main reason for the formation of the heat island effect.…”
Section: Introductionmentioning
confidence: 99%
“…For extractions of temperatures are used through various platforms such as ASTER, MODIS, NOAA/AVHRR, and LANDSAT [40]. For the distinction between urban and rural parts of the area is often used by the Land Use and Land Cover (LU/LC) layer derived from satellite images, with the proportion of impermeable surfaces often being used as the threshold between them [30,48,49] and/or the administrative boundaries of the city [50].…”
Section: Introductionmentioning
confidence: 99%
“…This area boasts a unique geographical location, abundant natural resources, and immense development potential, making it a subject of domestic and international attention. However, the development and construction process in this area has given rise to many ecological and environmental problems, such as the urban heat island effect [24][25][26], soil pollution [27], and increased disaster risks [28][29][30], which are at odds with the core principles of ecological protection and high-quality, eco-friendly development. Therefore, in order to promote ecological protection and high-quality development in the Yellow River Basin and the delta region, it is essential to accurately, timely, and comprehensively understand the spatiotemporal distribution and evolution trend of the ecological environment quality in the Yellow River Basin.…”
Section: Introductionmentioning
confidence: 99%